Significant Clinical Manifestations in Ballantyne Syndrome, after a Case Report and Literature Review: Recognizing Preeclampsia as a Differential Diagnosis - Navarro-Perez, Silvia F. (Case Rep Obstet Gynecol, 2019)
Ballantyne syndrome (BS) also called mirror syndrome is defined by the presence of a clinical triad that includes fetal hydrops and placental and maternal edema. Here we present a clinical case of a 34-year-old woman with a 29 weeks' pregnancy, who developed BS and fetal loss probably due to failure in prompt recognition of a rapidly growing sacrococcygeal teratoma (SCT). Due to similarities in clinical presentation with preeclampsia and the importance in early identification of the source for BS, we underwent a literature review in order to identify significant signs and symptoms, as well as sonographic changes, in order to help clinicians to make this prompt recognition, identification of the cause, and early management of BS, which will have an important impact in maternal and fetal survival.